Advances in hybrid conducting polymer technology - Shahabuddin, Syed; Pandey, Adarsh Kumar; Khalid, Mohammad; Jagadish, Priyanka (Springer, 2021)
This book presents synthesis methods, characterization techniques, properties and applications of hybrid conducting polymers. Special emphasis is given to the applications of hybrid conductive polymers, with chapters ranging from electronic devices, environmental remediation, and sensors, to medical applications.